Age-specific oxidative status and the expression of pre- and postcopulatory sexually selected traits in male red junglefowl, Gallus gallus. - Noguera, J; Dean, R; Isaksson, C; Velando, A; Pizzari, T (2012)
Oxidative stress is emerging as a key factor underpinning life history and the expression of sexually selected traits. Resolving the role of oxidative stress in life history and sexual selection requires a pluralistic approach, which investigates how age affects the relationship between oxidative status (i.e., antioxidants and oxidative damage) and the multiple traits contributing to variation in reproductive success. Here, we investigate the relationship between oxidative status and the expression of multiple sexually selected traits in two-age classes of male red junglefowl, Gallus gallus, a species which displays marked male reproductive senescence. We found that, irrespective of male age, both male social status and comb size were strongly associated with plasma oxidative status, and there was a nonsignificant tendency for sperm motility to be associated with seminal oxidative status. Importantly, however, patterns of plasma and seminal antioxidant levels differed markedly in young and old males. While seminal antioxidants increased with plasma antioxidants in young males, the level of seminal antioxidants remained low and was independent of plasma levels in old males. In addition, old males also accumulated more oxidative damage in their sperm DNA. These results suggest that antioxidant allocation across different reproductive traits and somatic maintenance might change drastically as males age, leading to age-specific patterns of antioxidant investment.